The mobility of modernism : art and criticism in 1920s Latin America - Montgomery, Harper (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture., 2017)
Many Latin American artists and critics in the 1920s drew on the values of modernism to question the cultural authority of Europe. Modernism gave them a tool for coping with the mobility of their circumstances, as well as the inspiration for works that questioned the very concepts of the artist and the artwork and opened the realm of art to untrained and self-taught artists, artisans, and women. Writing about the modernist works in newspapers and magazines, critics provided a new vocabulary with which to interpret and assign value to the expanding sets of abstracted forms produced by these artists, whose lives were shaped by mobility. Harper Montgomery examines modernist artworks and criticism that circulated among a network of cities, including Buenos Aires, Mexico City, Havana, and Lima. She maps the dialogues and relationships among critics who published in avant-gardist magazines such as Amauta and Revista de Avance and artists such as Carlos Merida, Xul Solar, and Emilio Pettoruti, among others, who championed esoteric forms of abstraction. She makes a convincing case that, for these artists and critics, modernism became an anticolonial stance which raised issues that are still vital today-the tensions between the local and the global, the ability of artists to speak for blighted or unincorporated people, and, above all, how advanced art and its champions can enact a politics of opposition.